Green Supply Chain Management Practices as Drivers of Environmental Sustainability: An Empirical Study of Manufacturing Firms in Nigeria - Sajuyigbe, Ademola Samuel; Abiodun, Oyewole Felicia; Igwe, Clara Obiageri; Arowoogun, Mokayode; Olufemi, Ayanda John; Akinbobola, Abiola Olubunmi (Program MM Universitas Surabaya, 2026)
Purpose: This research examines how Green Supply Chain Management (GSCM) strategies—Green Purchasing (GP), Environmental Collaboration with Suppliers (ECS), and Reverse Logistics (RL)—affect Environmental Performance (EP) in Nigerian manufacturing companies. Using the Resource-Based View (RBV) and the Institutional Theory, the study explores how internal strengths and external pressures influence sustainable supply chain adoption. Method: The study employed a purposive sampling technique to select four manufacturing firms in Oyo State: Nigerian Breweries Plc, Nigerian Bottling Company, P&G Plc, and Bond Pharmaceutical Company. Within these firms, simple random sampling was used to select individual respondents. In total, 205 employees participated in the survey, and the research utilised Structural Equation Modelling (SEM) to analyse the connections between these factors. Result: The findings demonstrate that GP, ECS, and RL all significantly and positively contribute to environmental performance, with green purchasing showing the greatest influence. Furthermore, the study found a high level of awareness of GSCM practices among the surveyed firms, suggesting considerable potential for effective implementation. This study adds to the current body of knowledge by offering empirical data from a developing nation's perspective and provides actionable advice for businesses and policymakers aiming to improve sustainability through comprehensive GSCM approaches.